Tingkat kesiapan dan faktor-faktor yang berpengaruh dalam menghadapi ujian nasional pada siswa SMP Negeri 1 Ayah tahun pelajaran 2014 / 2015 - Jaka Waluya (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
This study aims at: (1) Knowing how the level of preparedness for the National Exam in Mathematics, (2) Determining the internal factors of the students what influence the readiness to face national exam mathematics, and (3) Knowing the contribution of each variable are supposed to influence the level of preparedness of students for national examinations in Mathematics. This research has conducted the Students of State Junior High School 1st Ayah. The population was a class IX student of the Students of State Junior High School 1st Ayah totaled 252 students. The sampling technique used is proportional random sampling. Sample size determination used a formula developed by Slovin. The size of the sample was 155 students. Data collection techniques used methods of documentation and questionnaires. Data were analyzed using Multiple Regression Analysis and Partial Correlation. Based on the results of research are: (1) The level of preparedness of in National Examination Mathematics at were high, (2) internal factors, such as the level of anxiety, the intensity of learning, the availability of learning facilities, family support, and (3) Contributions / contribution of each variable is supposed to influence, for example: the relative contribution (SR) mastery of the material (X ) of 45.8%, the relative contribution (SR) level of anxiety (X2) by 1.6%, the relative contribution (SR ) the intensity of study (X3) of 28.9%, the relative contribution (SR) availability of learning facilities (X4) of 10.8%, and the relative contribution (SR) family support (X5) by 13.0%. While effective contribution (SE) mastery of the material (X1) of 28.82%, the effective contribution (SE) variable levels of anxiety (X2) by 0.99%, the effective contribution (SE) the variable intensity of learning (X3) amounted to 18.18 %, effective contribution (SE) availability of learning facilities (X ) of 6.80%, and the effective contribution (SE) family support (X ) of 8.19%.